2006
DOI: 10.1074/mcp.m600065-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Transforming Growth Factor-β Receptor-mediated Smad Signaling Complexes Analyzed by Mass Spectrometry

Abstract: ASmad proteins are the central feature of the transforming growth factor-beta (TGF-beta) intracellular signaling cascade. They function by carrying signals from the cell surface to the nucleus through the formation of a series of signaling complexes. Changes in Smad proteins and their complexes upon treatment with TGF-beta were studied in mink lung epithelial (Mv1Lu) cell cultures. A time course of incubation with TGF-beta was carried out to determine the peak of appearance of phosphorylated Smad2. Immobilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…One approach to further understand the selectivity is to identify proteins that uniquely interact with Smad2 or Smad3. Previous reports have identified novel Smad2 and/ or Smad3 protein-protein interactions with techniques including yeast two-hybrid assays [Akiyoshi et al, 1999;Verschueren et al, 1999;Wotton et al, 1999;Lin et al, 2000;Chen et al, 2002b;Ellis et al, 2003;Warner et al, 2003aWarner et al, ,b, 2004Colland et al, 2004;Wicks et al, 2005;Richard et al, 2006], luminescence-based mammalian interactome mapping (LUMIER) [Barrios-Rodiles et al, 2005], and immunoprecipitation of endogenous [Luo et al, 2006] and epitope-tagged Smad proteins Knuesel et al, 2003;Grimsby et al, 2004] combined with mass spectrometry. These studies identified proteins that play important roles in Smad-mediated TGF-b signaling such as c-SKI, SMURF2, SNON.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to further understand the selectivity is to identify proteins that uniquely interact with Smad2 or Smad3. Previous reports have identified novel Smad2 and/ or Smad3 protein-protein interactions with techniques including yeast two-hybrid assays [Akiyoshi et al, 1999;Verschueren et al, 1999;Wotton et al, 1999;Lin et al, 2000;Chen et al, 2002b;Ellis et al, 2003;Warner et al, 2003aWarner et al, ,b, 2004Colland et al, 2004;Wicks et al, 2005;Richard et al, 2006], luminescence-based mammalian interactome mapping (LUMIER) [Barrios-Rodiles et al, 2005], and immunoprecipitation of endogenous [Luo et al, 2006] and epitope-tagged Smad proteins Knuesel et al, 2003;Grimsby et al, 2004] combined with mass spectrometry. These studies identified proteins that play important roles in Smad-mediated TGF-b signaling such as c-SKI, SMURF2, SNON.…”
Section: Discussionmentioning
confidence: 99%
“…The whole protocol of protein in-gel digestion is the same as performed before (45) except that two steps, protein reduction and alkylation, were excluded in this experiment. The matrix-assisted laser desorption ionization (MALDI) mass spectrometric analysis of supernatants from in-gel digestion, and database searches were performed as before (45). Some identifications were checked with mass spectrometry (MS)/MS to screen the case, more than one protein in one spot.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 lists proteins identified using PMF and LC-MS/MS. All listed proteins meet the current stringent criteria for positive identifications (45,81). The proteins in the table are identified as upregulated or downregulated from sham-operated control to nodule-enriched neoplastic liver.…”
Section: -De Maps For Liver Tissue Proteomementioning
confidence: 99%
“…E1B-AP5 is a multifunctional protein; in addition to its role in mRNA metabolism, it may play a part in transcriptional regulation via interactions with transcription factors such as bromodomain-containing protein 7 (BRD7), p53, and small and mothers against decaplentaplegic-related protein 2 (SMAD2) (7,85,96). By using transient reporter assays, it was shown that E1B-AP5 is a repressor of basal transcription driven by several cellular and viral promoters (85).…”
Section: E1b-55k and Cellular Binding Proteinsmentioning
confidence: 99%